Effect of Si element on phase transformation and mechanical properties for FeCoCrNiSix high entropy alloys - Huang, Lei; Wang, Xuejie; Jia, Fuchao; Zhao, Xingchuan; Huang, Baoxu; Ma, Jie; Wang, Changzheng (Materials letters, 2021)
•The addition of Si element is beneficial for the formation of BCC phase.•Si1.0 HEAs has the highest micro-hardness and the best wear resistance.•The wear mechanism changes from oxidation wear and abrasive wear to abrasive wear. In present research, the phase evolution and mechanical properties of FeCoCrNiSix high-entropy alloys were investigated by using different testing techniques. The results showed that Si element can promote the formation of BCC phase and had a significant effect on the micro-hardness and wear resistance of alloys. The micro-hardness of HEAs increased from 89.52 HV to 653.71 HV and the depth of the wear track decreased from 22.139 μm to 5.292 μm with the addition of Si element. When x was equal to 1 (FeCoCrNiSix), the alloy possessed the highest micro-hardness and best wear resistance. Moreover, the wear mechanism was transformed into abrasive wear according to the wear tracks measurements due to the addition of Si elements.